Outcomes of Venus P-valve for dysfunctional right ventricular outflow tracts from Indian Venus P-valve database - Kothandam Sivakumar; Pramod Sagar; Shakeel Qureshi; Worakan Promphan; Bijulal Sasidharan; Neeraj Awasthy; Mahesh Kappanayil; Pujar Venkatesh Suresh; Nageswara Rao Koneti (Wolters Kluwer Medknow Publications, 2021)
Background : Balloon-expandable pulmonary valves are usually not suitable for dilated native outflow tracts. Methods : Indian Venus P-valve registry was retrospectively analyzed for efficacy, complications, and midterm outcomes. Straight valve was used in prestented conduits in patients with right ventricular pressure above two-thirds systemic pressure and/or right ventricular dysfunction. Flared valve 1-4 mm larger than balloon waist was used in native outflow in symptomatic patients, large ventricular volumes, and ventricular dysfunction. Objectives : A self-expanding porcine pericardial Venus P-valve is available in straight and flared designs.. Results : Twenty-nine patients were included. Straight valve was successful in all seven conduits, reducing gradients significantly, including one patient with left pulmonary artery (LPA) stent. Flared valve was successfully implanted in 20 out of 22 native outflow tracts. Sharp edges of the older design contributed to two failures. Complications included two migrations with one needing surgery, endocarditis in one, insignificant wire-frame fractures in three, and groin vascular complication in one patient. There were no deaths or valve-related reinterventions at a mean follow-up of 47.8 ± 24.5 months (1-85 months). Modifications of technique succeeded in three patients with narrow LPA. There was significant improvement in symptoms, right ventricular volume, and pulmonary regurgitant fraction. Conclusion : Straight and flared Venus P-valves are safe and effective in appropriate outflow tracts. Straight valve is an alternative to balloon-expandable valves in stenosed conduits. Flared valve is suitable for large outflows up to 34 mm, including patients with LPA stenosis. Recent design modifications may correct previous technical failures. Studies should focus on durability and late complications.